Sonja Vermeulen, Head of Research, interviewed - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Sonja Vermeulen, CCAFS Head of Research is being interviewed as part of her presentation at the 29 Brussels Briefing in September, 2012. Read more about the event on the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) blog: https://ccafs.cgiar.org/blog/looking-beyond-agriculture-help-create-resilient-smallholder-farms